Simulation Research of the n-Butanol Proportion Influence on HCCI Combustion of Free-Piston Diesel Engine Generators - Chunhui Liu; Hao Zheng (International Journal of Chemical Engineering)
For researching the influence of n-butanol proportion in diesel fuel on homogeneous charge compression ignition (HCCI) combustion of the free-piston diesel engine generator (FPDEG), a three-dimensional (3D) moving mesh computational fluid dynamics (CFD) simulation model of a FPDEG prototype was developed. A detailed chemical reaction mechanism of diesel fuel was selected as the HCCI combustion mechanism and coupled in the established HCCI combustion simulation model of the FPDEG prototype. The validity of the established HCCI combustion simulation model is proved by comparing the simulation and experimental pressure curves under the condition of pure diesel fuel. The simulation results of different n-butanol proportions in diesel fuel showed that as the n-butanol proportion increased from 0 to 60%, the maximum heat release rate decreased to 59.6 J/deg, the calculated indicated thermal efficiency augmented to 4.6%, the calculated indicated mean effective pressure increased to 0.057 MPa, and the final NOx and CO content decreased to 0.239 and 0.57 g/kg fuel, respectively, but the final soot content increased to 0.000562 g/kg fuel. Therefore, the n-butanol proportion of diesel fuel played a vital role in combustion and emission progress of the FPDEG.